Practicing Peace, Preaching Psalms: The Centrality of the Enarrationes in Psalmos to Augustine's Developing Theological Understanding of Peace - Grove, Kevin G. (Editorial Uniagustiniana, 2019)
This chapter claims that while the subject of peace permeates the Augustinian corpus, Augustine's theological understanding of peace-which progressed from an absence of conflict to the graced concord of love as the whole Christ-developed as he labored to preach on the Psalms. Augustine began to preach on the Psalms in the 390s and continued to do so for the rest of his life, rendering his Enarrationes in Psalmos his longest work. The Psalms, replete with the language of peace -interior and exterior peace as well as the peace of Jerusalem- were the texts Augustine regularly exposited as he preached ad populum in his own Basilica of Peace. By looking at Augustine's theology of peace through the Enarrationes, the chapter shows that peace as it appears in his preaching is only fully understood for Augustine when seen through his Christology. The Enarrationes in Psalmos provide evidence of the practice of peace. Augustine suggests earthly peace and love might be exercised both within his congregation and among the dwellers of North Africa of the fifth century. Having examined the Enarrationes themselves, the chapter suggests the relevance of this reading for two other texts, considering the examples of an early and a late treatment of peace: de Sermone Domini in Monte and De civitate Dei, respectively